The estimated glomerular filtration rate predicts pacemaker-induced cardiomyopathy - Mitsunori Oida; Eriko Hasumi; Goto Kohsaku; Kani Kunihiro; Tsukasa Oshima; Takumi J. Matsubara; Jun Matsuda; Yu Shimizu; Gaku Oguri; Toshiya Kojima; Katsuhito Fujiu; Issei Komuro (Scientific Reports, 2023)
Abstract Clinical predictors for pacemaker-induced cardiomyopathy (PICM) (e.g., a wide QRS duration and left bundle branch block at baseline) have been reported. However, factors involved in the development of PICM in patients with preserved left ventricular ejection fraction (LVEF) remain unknown. This study aimed to determine the risk factors for PICM in patients with preserved LVEF. The data of 113 patients (average age: 71.3 years; men: 54.9%) who had echocardiography before and after pacemaker implantation (PMI) among 465 patients undergoing dual-chamber PMI were retrospectively analyzed. Thirty-three patients were diagnosed with PICM (18.0/100 person-years; 95% CI 12.8–25.2). A univariate Cox regression analysis showed that an estimated glomerular filtration rate (eGFR) ≤ 30 mL/min/1.73 m2 (HR 3.47; 95% CI 1.48–8.16) and a past medical history of coronary artery disease (CAD) (HR 2.76; 95% CI 1.36–5.60) were significantly associated with the onset of PICM. After adjusting for clinical variables, an eGFR ≤ 30 mL/min/1.73 m2 (HR 2.62; 95% CI 1.09–6.29) and a medical history of CAD (HR 2.32; 95% CI 1.13–4.80) were independent risk factors for developing PICM. A medical history of CAD and low eGFR are independent risk factors for PICM in patients with preserved LVEF at baseline. These results could be helpful in predicting a decreased LVEF by ventricular pacing before PMI. Close follow-up by echocardiography is recommended to avoid a delay in upgrading to physiological pacing, such as cardiac resynchronization therapy or conduction system pacing.